Integration of high-resolution imaging and minimally invasive ablation in the resection of thyroid microcarcinomas: evaluation of surgical precision and functional outcomes - Zuluaga, Mauricio Zuluaga; Jiménez, Melanie Victoria Gavilanez; Cervantes, Elida Elizabeth Alvarado; Gastelum, Jorge Luis Rivera; Jiménez, Maria Luisa Guerrero; Muriel, Santiago Zuluaga; Cabello, Diego Andres Valdes; Noriega, David Bernardo García (International Journal of Research in Medical Sciences, 2024)
Since high-resolution imaging and minimally invasive ablation techniques have emerged, their integration in medical field has marks a significant advancement in oncology including thyroid microcarcinomas (TMCs) management. TMCs are small but potentially aggressive tumors. TMCs require precise intervention to balance oncologic control and thyroid function preservation. Such as the detailed ultrasonic MRI and CT scan has improved TMC’s diagnostic ability and especially, the surgery planning. They are now making it possible to map tumors and the tumor margins in real time. Technological advances to minimally invasive ablation approaches such as radiofrequency and microwave ablation (MWA) have now shifted to offer localized cancer tissue destruction with less complications than the classical thyroidectomy. These techniques produce superior functional outcomes such as voice preservation and reduced hypoparathyroidism rates as well as high procedural success rates of more than 90%. Combining sophisticated imaging and ablation increases precision while resulting in recurrence rates as low as 2-5% in low-risk individuals. Despite these developments some challenges such as operator dependency and expensive costs that limit accessibility. Evidence supports the use of these approaches as an alternative to traditional surgery for certain patients showing importance of competent operators and technological infrastructure. This paradigm shift not only improves TMC treatment, but it also necessitates additional study to maximize long-term outcomes and increase accessibility. Ethical adherence and rigorous methodologies ensure reliable evaluations of safety efficacy, and functional outcomes. Evidence supports the integration of these techniques as an alternative to conventional surgery for select patients, emphasizing the need for skilled operators and technological infrastructure. This Transformation not only refines TMC management but also warrants continued research to optimize long-term outcomes and broaden accessibility.